The world guide to CSR : a country-by-country analysis of corporate sustainability and responsibility - Visser, Wayne.; Tolhurst, Nick. (Greenleaf, 2010)
Provides comparable national profiles that describe the evolution and practice of corporate sustainability and responsibility (CSR) for 58 countries and 5 global regions. Each regional and national profile includes key information about the relevant CSR history, country-specific issues, trends, research and leading organisations. Each regional/country profile includes the following subsections: CSR in context, priority issues, trends, legislation and codes, organisations, case studies, educational institutions, references.--From publisher's description.